Derivatives
The tangent of a curve at a point:
Suppose that we have a Curve C, and we wish to get the equation of the
tangent line to a curve C at a given point P = (a, f(a)). Consider a point
Q = Q(x, y) which is near to the point P = (a, f(a)). The slope of PQ is
given by:
m
PQ
=
f(x) − f(a)
x − a
.
If x → a, then Q → P, and the slope of the tangent at P is given by:
m = lim
x→a
f(x) − f(a)
x − a
.
If the previous limit exists, it is called the derivative of the function f(x) at
the point a and it is denoted by f
(a).
The equation of the tangent and the normal
The equation of the tangent of a curve at a point (a, f(a)) is given by
y − f(a) = m(x − a), m = f

(a,f(a))
= lim
x→a
f(x) − f(a)
x − a
.
Moreover, the equation of normal at (a, f(a)) is
y − f(a) =
−1
m
(x − a), m = 0.
1
Def. The derivative for a function f(x), at x = a exists if lim
x→a
f(x) − f(a)
x − a
exists and in such case we write:
f
(a) = lim
x→a
f(x) − f(a)
x − a
= lim
h→0
f(a + h) − f(a)
h
Example 1. Find the equation of the tangent line and the normal line to the
function f(x) = x
3
at the point (2, 8).
Solution. The slope of the function f(x) = x
3
at the point (2, 8) is given by
m = lim
x→2
f(x) − f(2)
x − 2
= lim
x→2
x
3
− 8
x − 2
= lim
x→2
(x − 2) (x
2
+ 2 x + 4)
x − 2
= lim
x→2
(x
2
+ 2 x + 4) = 12,
so the equation of the tangent line is given by
y − y
1
= m(x − x
1
), where (x
1
, y
1
) is the given point and m is the slope,
so the equation is: y −8 = 12(x −2) = 0, or y −12 x + 16 = 0. The equation
of the normal at (2, 8) is given by
y − 8 =
−1
12
(x − 2),
which can be written as:
x + 12 y − 98 = 0.
Example 2. By the deﬁnition of the derivative, ﬁnd the derivative for the
following functions
(i) f(x) =
√
x
(ii) f(x) =
1
x − 5
2
(iii) f(x) = sin x
Solution:
(i) Let a ∈]0, ∞[. The derivative for a function at a is given by
f
(a) = lim
x→a
f(x) − f(a)
x − a
= lim
x→a
√
x −
√
a
x − a
= lim
x→a
(
√
x −
√
a) (
√
x +
√
a)
(x − a) (
√
x +
√
a)
= lim
x→a
x − a
(x − a) (
√
x +
√
a)
= lim
x→a
1
(
√
x +
√
a)
=
1
√
a +
√
a
=
1
2
√
a
.
Finally, the derivative for f(x) =
√
x for all x ∈]0, ∞[ is given by
f
(x) =
1
2
√
x
.
An alternative solution
Let x ∈]0, ∞[. The derivative for a function at x is given by
f
(x) = lim
h→0
f(x + h) − f(x)
h
= lim
x→a
√
x + h −
√
x
h
= lim
h→0
_√
x + h −
√
x
_ _√
x + h +
√
x
_
h
_√
x + h +
√
x
_ .
= lim
h→0
x + h − x
h
_√
x + h +
√
x
_ = lim
h→0
h
h
_√
x + h +
√
x
_ =
1
2
√
x
,
and so
f
(x) =
1
2
√
x
, x ∈]0, ∞[.
(ii) Let a ∈ R − {5}. The derivative for f(x) at a is given by
f
(a) = lim
x→a
f(x) − f(a)
x − a
= lim
x→a
1
x − 5
−
1
a − 5
x − a
= lim
x→a
(a − 5) − (x − 5)
(x − 5) (a − 5)
·
1
x − a
= lim
x→a
−(x − a)
(x − a) (x − 5) (a − 5)
= lim
x→a
−1
(x − 5) (a − 5)
=
−1
(a − 5)
2
.
3
Finally, the derivative for f(x) =
1
x − 5
for all x ∈ R − {5} is given by
f
(x) =
−1
(x − 5)
2
.
(iii) Let a ∈ R. The derivative for f(x) at a is given by
f
(a) = lim
x→a
f(x) − f(a)
x − a
= lim
x→a
sin x − sin a
x − a
= lim
x→a
2 sin
_
x − a
2
_
cos
_
x + a
2
_
x − a
= lim
x→a
2 sin
_
x − a
2
_
x − a
· cos
_
x + a
2
_
= lim
x−a→0
2 sin
_
x − a
2
_
x − a
· lim
x→a
cos
_
x + a
2
_
= lim
x−a
2
→0
sin
_
x − a
2
_
x − a
2
· lim
x→a
cos
_
x + a
2
_
= 1 · cos a = cos a.
Finally, the derivative for f(x) = sin x for all x ∈ R is given by
f
(x) = cos x .
Note: For all y ∈ R,
lim
y→a
cos y = cos a.
Example 3. Discuss the diﬀerentiability of each function at the given point:
1. f(x) = x (at x = 0).
2. f(x) = x
2
x (at x = 0).
4
3. f(x) = xx − 2 (at x = 2).
4. f(x) =
_
¸
¸
¸
_
¸
¸
¸
_
x
3
sin
_
1
x
_
, if x = 0;
0, if x = 0.
(at x = 0).
Solution:
(1) We test the existence of the limit:
lim
x→0
f(x) − f(0)
x − 0
= lim
x→0
x − 0
x − 0
= lim
x→0
x
x
.
Now:
lim
x→0
+
x
x
= lim
x→0
+
x
x
= 1,
but
lim
x→0
−
x
x
= lim
x→0
−
−x
x
= −1.
Hence, lim
x→0
x
x
does not exist and so the function x is not diﬀerentiable at
x = 0.
Note. Although the function is not diﬀerentiable at x = 0, it is continuous
at the same point. Thus we conclude that the continuity of a function at a
certain point does not imply the diﬀerentiability of it at the same point.
(2) We test the existence of the limit:
lim
x→0
f(x) − f(0)
x − 0
= lim
x→0
x
2
x − 0
2
0
x − 0
= lim
x→0
x
2
x
x
= lim
x→0
xx = 0.
Hence, lim
x→0
x
2
x
x
= 0 and so the function f(x) = x
2
x is diﬀerentiable at x = 0
and f
(0) = 0.
5
(3) We test the existence of the limit:
lim
x→2
f(x) − f(2)
x − 2
= lim
x→2
xx − 2 − 22 − 2
x − 2
= lim
x→0
xx − 2
x − 2
.
Now:
lim
x→2
+
xx − 2
x − 2
= lim
x→2
+
x(x − 2)
x − 2
= lim
x→2
+
x = 2,
but
lim
x→2
−
xx − 2
x − 2
= lim
x→2
−
−x(x − 2)
x − 2
= lim
x→2
+
−x = −2.
Hence, lim
x→2
xx − 2
x − 2
does not exist and so the function f(x) = xx − 2 is not
diﬀerentiable at x = 2.
(4) We test the existence of the limit:
lim
x→0
f(x) − f(0)
x − 0
= lim
x→0
x
3
sin
_
1
x
_
− 0
x − 0
= lim
x→0
x
2
sin
_
1
x
_
.
Since we have
−1 ≤ sin
1
x
≤ 1, ∀ x ∈ R − {0}
If we multiply by x
2
(x
2
> 0), we get
−x
2
≤ x
2
sin
1
x
≤ x
2
, ∀ x ∈ R − {0} .
By the Squeeze theorem and noting that lim
x→0
x
2
= lim
x→0
−x
2
= 0, Hence, f(x)
is diﬀerentiable at x = 0 and f
(0) = 0.
Theorem. If is diﬀerentiable at a, then it is continuous at a.
6
Note . The converse of the above theorem is false; that is, the continuity
of a function does not imply diﬀerentiability. For example for the function
f(x) = x, it is continuous at x = 0, since
lim
x→0
x = 0,
but it is not diﬀerentiable at x = 0 (see Example 3, part 1).
Rules of derivatives: In the following table, we summarize the rules of
derivatives. In this Table y denotes a function and y
denotes its derivative
Table 1: Rules of derivatives
y y
y y
c 0 x 1
√
x
1
2
√
x
1
x
−1
x
2
x
n
nx
n−1
c f(x) c f
(x)
f(x) + g(x) f
(x) + g
(x) f(x) − g(x) f
(x) − g
(x)
f(x) g(x) f(x) g
(x) + g(x) f
(x)
f(x)
g(x)
g(x) f
(x) − f(x) g
(x)
g
2
(x)
,
g(x) = 0
f(x) g(x) h(x) f(x) g(x) h
(x) + f(x) g
(x) h(x)
_
f(x)
f
(x)
2
_
f(x)
+f
(x) g(x) h(x)
(f(x))
α
α (f(x))
α−1
f
(x) (f ◦ g)
(x) f
(g(x)) · g
(x)
7
Some notes on Table 1:
• If c is a constant, compare between each derivative of the following func
tions
c, c f(x),
c
f(x)
,
f(x)
c
The derivatives are given, respectively by:
0, c f
(x),
−c f
(x)
f
2
(x)
,
f
(x)
c
• The chain rule:
(f ◦ g)
(x) = f
(g(x)) · g
(x).
• Compare between the composition of functions and the multiplication of
functions.
Example: Diﬀerentiate: f
1
(x) = sin (cos
2
x) and f
2
(x) = sin x (cos
2
x)
f
1
(x) is a composition, so its derivative is given by (Using the chain rule)
f
1
(x) = cos
_
cos
2
x
_
·
d
dx
_
cos
2
x
_
= cos
_
cos
2
x
_
·
d
dx
(cos x)
2
= cos
_
cos
2
x
_
· (2 cos x)
d
dx
(cos x)
= cos
_
cos
2
x
_
· (2 cos x) · (−sin x)
= −2 cos x sin x cos
_
cos
2
x
_
= −sin 2x cos
_
cos
2
x
_
,
while f
2
(x) is a multiplication of two functions, so its derivative is given
by:
f
2
(x) = sin x ·
d
dx
_
cos
2
x
_
+ cos
2
x ·
d
dx
(sin x)
= sin x · (−2 cos x sin x) + cos
2
x (cos x) = −2 sin
2
x cos x + cos
3
x.
8
• In some problems, it is desirable to abbreviate the function before dif
ferentiation.
Example: Diﬀerentiate the function: f(x) =
_
sin
2
3x + cos
2
3x
_
105
x
Using the trigonometric identity sin
2
θ + cos
2
θ = 1, so f(x) =
1
x
, and
hence its derivative is f
(x) =
−1
x
2
.
Table 2: Derivatives of Trigonometric functions
y y
y y
sin x cos x cos x −sin x
tan x sec
2
x cot x −csc
2
x
sec x sec x tan x csc x −csc x cot x
sin f(x) f
(x) cos f(x) cos x −f
(x) sin f(x)
tan f(x) f
(x) sec
2
f(x) cot f(x) −f
(x) csc
2
f(x)
sec f(x) f
(x) sec f(x) tan f(x) csc f(x) −f
(x) csc f(x) cot f(x)
Some comments on Table 2
• By def. of the derivative, one can show that the derivatives of sin x and
cos x are given by:
d
dx
sin x = cos x,
d
dx
cos x = −sin x.
• The derivative of the trigonometric functions tan x, cot x, sec x, csc x,
can be easily evaluated by means of the quotient rule for derivative.
9
For example:
d
dx
tan x =
d
dx
_
sin x
cos x
_
=
cos x
d
dx
(sin x) − sin x
d
dx
(cos x)
cos
2
x
=
cos
2
x + sin
2
x
cos
2
x
=
1
cos
2
x
= sec
2
x.
Example 4: Find the ﬁrst derivative for the following functions
(1) f(x) = x
2
sin x + x
3
tan x (2) f(x) = x
√
x
2
+ 1 cos(5x)
(3) f(x) = cos
_
tan
_√
x
__
(4) f(x) =
cos x
cos x + sin x
(5) f(x) =
7
√
sec x + 1 + sin x
3
(6) f(x) =
_
x +
_
x +
√
x
Solution
(1) f
(x) =
d
dx
_
x
2
sin x
_
+
d
dx
_
x
3
tan x
_
= x
2
cos x + 2x sin x + x
3
sec
2
x + 3 x
2
tan x.
(2) f
(x) =
d
dx
_
x
√
x
2
+ 1 cos(5x)
_
=
d
dx
(x)
√
x
2
+ 1 cos(5x) + x
d
dx
_
√
x
2
+ 1
_
cos(5x) + x
√
x
2
+ 1
d
dx
(cos(5x))
= 1 ·
√
x
2
+ 1 cos(5x) + x
2 x
2
√
x
2
+ 1
cos(5x) + x
√
x
2
+ 1 · (−5 sin(5x))
=
√
x
2
+ 1 cos(5x) +
x
2
√
x
2
+ 1
cos(5x) − 5 x
√
x
2
+ 1 sin(5x).
(3)‘ f
(x) =
d
dx
cos
_
tan
_√
x
__
= −sin
_
tan
_√
x
__
·
d
dx
_
tan
_√
x
__
= −sin
_
tan
_√
x
__
· sec
2
_√
x
_
1
2
√
x
.
10
(4) f
(x) =
d
dx
_
cos x
cos x + sin x
_
=
(cos x + sin x) (−sin x) − cos x (−sin x + cos x)
(cos x + sin x)
2
=
−cos x sin x − sin
2
x + cos x sin x − cos
2
x
(cos x + sin x)
2
−
_
sin
2
x + cos
2
x
_
(cos x + sin x)
2
=
−1
(cos x + sin x)
2
(5) f
(x) =
d
dx
_
7
√
sec x + 1
_
+
d
dx
sin x
3
=
1
7
(sec x + 1)
−
6
7
d
dx
(sec x + 1) + cos x
3
·
d
dx
(x
3
)
=
1
7
(sec x tan x) (sec x + 1)
−
6
7
+ 3x
2
cos x
3
.
(6) f
(x) =
1
2
_
x +
_
x +
√
x
·
d
dx
_
x +
_
x +
√
x
_
=
1
2
_
x +
_
x +
√
x
·
_
1 +
1
2
_
x +
√
x
·
d
dx
_
x +
√
x
_
_
=
1
2
_
x +
_
x +
√
x
·
_
1 +
1
2
_
x +
√
x
·
_
1 +
1
2
√
x
_
_
An application to the derivative (Velocity):
Suppose an object moves along a straight line according to an equation of
motion, where is the displacement (directed distance) of the object from the
origin at time t. The function that describes the motion is called the position
function of the object. In the time interval [a, a + h]. The average velocity
over this time interval is
Average velocity =
displacement
time
=
f(a + h) − f(a)
h
.
11
The instantaneous velocity at t = a is given by:
v(a) = lim
h→0
f(a + h) − f(a)
h
12
Higher Derivatives
Let y
(x) =
dy
dx
denote the ﬁrst derivative to y with respect to x, then we
deﬁne:
y
(x) =
dy
dx
=
d
2
y
dx
2
(the second derivative), and
y
(x) =
dy
dx
=
d
3
y
dx
3
(the third derivative), and so on.
Example 5: Find y
for the function:
y =
√
x tan x + cos
5
(π x)
Solution: Since y =
√
x tan x + (cos(π x))
5
, so
y
=
√
x sec
2
x +
tan x
2
√
x
+ 5 (cos(π x))
4
· (−sin πx) · π
∴ y
=
√
x sec
2
x +
tan x
2
√
x
− 5 π sin πx · (cos(π x))
4
.
Now
y
=
√
x (2 sec x) (sec x tan x) +
sec
2
x
2
√
x
+
2
√
x sec
2
x −
tan x
√
x
4 x
− 5 π
_
sin πx · 4 (cos(π x))
3
· (−π sin π x) + (cos(π x))
4
π cos π x
_
∴ y
=2
√
x sec
2
x tan x +
sec
2
x
2
√
x
+
2
√
x sec
2
x −
tan x
√
x
4 x
− 5 π
2
_
− 4 sin
2
πx cos
3
(π x) + cos
5
πx
_
∴ y
=2
√
x sec
2
x tan x +
sec
2
x
2
√
x
+
2
√
x sec
2
x −
tan x
√
x
4 x
+ 5 π
2
cos
3
π x(4 sin
2
πx − cos
2
πx).
13
Implicit Diﬀerentiation:
Let us compare between:
y = x
2
√
x + tan x
3
(1)
x y = tan(x y
2
) (2)
In (1), y is expressed explicitly in terms of x, while y in (2) is expressed
implicitly in terms of x, so in (2) y is implicit function of x.
Notes:
• In some problems, it is not easy to express y explicitly in terms of x.
• If y is an implicit function of x, then
d
dx
_
y
3
_
=
dz
dx
, z = y
3
∴ By the chain rule:
d
dx
_
y
3
_
=
dz
dy
dy
dx
= 3 y
2
dy
dx
.
Example 6: If x
7
+ y
3
= 12, ﬁnd y
Solution: If we diﬀerentiate both sides w.r.t x, we get
7 x
6
+ 3 y
2
y
= 0,
so
y
=
−7 x
6
3 y
2
, y = 0.
Example 7: Find y
, if y
3
− x
2
= 4.
Solution: If we diﬀerentiate both sides w.r.t x, we get
3 y
2
y
− 2 x = 0,
14
so
y
=
2 x
3 y
2
, y = 0
Now
y
=
d
dx
(y
) =
3 y
2
(2) − 2 x(6 y y
)
9 y
4
=
6 y
2
− 12 x y y
9 y
4
=
6 y
2
− 12 x y
_
2 x
3 y
2
_
9 y
4
=
6 y
2
− 8
_
x
2
y
_
9 y
4
∴ y
=
6 y
3
− 8x
2
9 y
5
, y = 0.
Example 8: Find y
, if cos(x − y) = (2x + 1)
3
y.
Solution: Diﬀerentiating implicitly w.r.t x, we have
− sin(x − y) [1 − y
] = (2x + 1)
3
y
+ 3 (2x + 1)
2
2 y
∴ −sin(x − y) + y
sin(x − y) = (2x + 1)
3
y
+ 6 (2x + 1)
2
y
∴ y
_
sin(x − y) − (2x + 1)
3
¸
= 6 (2x + 1)
2
y + sin(x − y)
∴ y
=
6 (2x + 1)
2
y + sin(x − y)
sin(x − y) − (2x + 1)
3
.
Example 9: Given that
y = (x
2
− 1)
n
,
show that
(x
2
− 1) y
− 2(n − 1) x y
− 2ny.
Solution: Since, y = (x
2
− 1)
n
, then if we diﬀerentiate with respect to x, we
15
get
y
= n(x
2
− 1)
n−1
· 2 x = 2 nx(x
2
− 1)
n−1
∴ y
= 2 nx(x
2
− 1)
n−1
·
x
2
− 1
x
2
− 1
(Multiply both numerator and denominator by x
2
− 1)
∴ y
=
2 nx(x
2
− 1)
n
x
2
− 1
=
2 nxy
x
2
− 1
∴ (x
2
− 1) y
= 2 nxy.
Diﬀerentiating the last equation with respect to x, we get
(x
2
− 1) y
+ 2 x y
= 2 n(x y
+ y(1))
∴ (x
2
− 1) y
+ 2 x y
− 2 nxy
− 2 ny = 0
Finally
(x
2
− 1) y
− 2(n − 1) x y
− 2ny = 0.
Example 10: Find an equation for the tangent and the normal lines to the
curve
x
3
+ y
3
= 1 + 3 x y
2
at (2,1)
Solution: First note that (2, −1) is on the curve, since
2
3
+ (−1)
3
= 7 = 1 + 3(2)(−1)
2
.
Diﬀerentiating the given equation implicitly w.r.t x, we get
16
3 x
2
+ 3 y
2
y
= 3 x(2 y y
) + 3 y
2
x
2
+ y
2
y
= 2 x y y
+ y
2
(dividing by 3)
If we set x = 2, y = −1, we get 4 + y
= −4 y
+ 1
and therefore 3 = −5 y
∴ y

(2,−1)
=
−3
5
.
Now, the slope of the tangent is m =
−3
5
, and the slope of the normal is
−1
m
=
5
3
, and so the equation of the tangent is given by:
y − (−1) =
−3
5
(x − 2), which gives y + 1 =
−3
5
(x − 2),
while the equation of the normal is given by:
y + 1 =
5
3
(x − 2).
17